Análise dialógica e ensino de língua portuguesa para universitários - Cavalcante, Cláudia Garcia (2014)
In this thesis, we deal with the teaching of the Portuguese language in higher education, taking into consideration the course book as the discursive space that allows us to better understand the construction of authorship a dimension that involves particular work processes with language. Such processes contribute to the teaching of writing to undergraduate students. Our perspective of development of the thesis is dialogic. Therefore, we described, analyzed and interpreted the reflexes of the dialogic language as we read from the works of Bakhtin and the Circle in the course book Prática de texto para estudantes universitários (Petrópolis: Editora Vozes, 2011/1992) (PTEU) written by Carlos Alberto Faraco and Cristovão Tezza, authors who are well known by their Bakhtinian affiliation. This material was chosen mainly because of the theoretical commitment of the authors-creators, based on dialogism and on the constitutive socio-historical relation I-other, as well as by the foreword of the book, which proposes a treatment to written language followed by discursive reflections that enable the students to learn in the light of the multiple social languages that surround them. In order to situate this material in a wider sphere, we aimed at some knowledge about the educational profile of the high school alumni, by means of large scale examinations, like ENEM and PISA. After that, we investigated the Brazilian Higher Education organization and the selection of courses of those starting it. Aware of these, we establish a dialog with the National Curriculum Guidelines (Diretrizes Curriculares Nacionais, in Portuguese) of the most popular courses in the country so as to draw a profile of the projected abilities for the first year students. Yet as our preliminary investigation, we researched the language teaching materials available in the market, which try to adjust the student to the demands of academic writing. Thus, in the process of building our research object, we established the following premises: a) acknowledgement that there is a gap between the profile of those graduating in high school and those expected to start higher education, especially in the sense of their linguistic, communicative and discursive abilities. b) acknowledgement that the production of educational material to teach Portuguese to those students mobilizes linguistic aspects that, somehow, reflect and refract the aforementioned gap. c) acknowledgement that there is an inseparable relationship between language and ethics, which results in a pedagogy committed to the formation of citizens that are readers and producer of texts. From these premises, we ground our concept of language on Bakhtin and the Circle, to whom every utterance is produced in a social, historical and cultural context, as a concrete utterance in relation to production, reception and circulation of texts among socially organized subjects. From this theoretical perspective, notions of authorship and discursive interaction are used as analytical categories that allow us to access the corpus that consists of the chapters about teaching the discursive genres and the textual production exercises. Having these categories, the methodology departed from a methodological-theoretical exercise, whose objective was to establish a dialog between the corpus and the theoretical individual work of each author, by observation of the macro construction, followed by the same process with the organization of the parts that compose the didactic set. This procedure reflects our central hypothesis that the theoretical alignment of an author changes the concrete utterances, which springs from the working with language in the construction of practical exercises of writing. In order to pursue this hypothesis, we aim at investigating whether the author, overtly Bakhtinian in his theoretical approach, siding with the dialogic perspective of language, promotes in his coursebook, a space for the construction of authorship and contributes to the teaching of writing to university students. To observe this aspect, our work was guided by the central concept to the dialogic theory of language, i.e, interaction, and by the question that we formulated: in what ways have the traces of interlocution instated between author and student/reader led the exercises proposed in PTEU, reflecting and refracting the theoretical positioning of the author? The analyses led by the kernel aspect represented by such issue confirmed our thesis: the positioning of the author is decisive to construct the work as the discursive space that allows the understanding of the construction of authorship and, most importantly, as an inseparable space between language and ethics, which reflects as a pedagogy committed to the formation of the citizen who is a reader and producer of texts. We hope that this study is theoretically and practically relevant to the field of Applied Linguistics and the studies of language, as well as to the possibility of establishing a relationship between the Bakhtinian theory and its practice